Komposisi Jenis dan Tutupan Lamun di Perairan Dusun Pandanan, Sekotong, Lombok Barat - Rahfika, Rahfika; Rahman, Ibadur; Paryono, Paryono (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
Seagrasses can live on muddy, sandy and broken coral or rock substrates. Seagrass ecosystems are often found in areas with thick sandy mud substrates. Seagrass beds are one of the aquatic ecosystems that have high water productivity, and have a vital role for the associated biota that live around them, both as a feeding ground, nursery ground, and spawning ground. The purpose of this study was to see the species composition and cover of seagrass species in the waters of Pandanan Hamlet, Sekotong, West Lombok. Seagrass data collection was carried out at low tide, using the line transect method by making the observation path into three replicates with a length of 100 m each, a distance of 50 m each transect. The 50 cm quadrat frame is placed on the right side of the transect with a distance of 10 m between one quadrant and the other so that the total quadrant on each transect is 11 quadrants. The results showed that the composition of seagrass species found in the waters of Pandanan Hamlet, Sekotong, West Lombok as many as 7 (seven) seagrass species, namely: S. isoetifolium, C. rotundata, E. acoroides, T. hemprichii, H. ovalis, H. uninervis and H. pinifolia with Seagrass Cover in the Waters of Pandanan Hamlet Sekotong, Lombok is included in the category of moderate and rare with the percentage of seagrass species S. isoetifolium (2.78%-9.36%), C. rotundata (1.39%-6.91%), E. acoroides (7.03%-14.75%), Thalassia hemprichii (2.31%-9.66%), H. ovalis (2.5%-0.98%), H. uninervis (0.038%) and H. pinifolia (4.64%). The index of importance at the 2 stations had different values. The type of E. acoroides has the highest INP value at both stations, with values of 61.54% and 62.06% respectively. Ecological Index in the Waters of Pandanan Hamlet, Sekotong, West Lombok includes: Seagrass Diversity Index with the value obtained (1.43 and 1.65). Diversity Index with values (0.8 and 0.92) and Dominance Index with values (0.26 and 0.22).